2018
DOI: 10.5688/ajpe6299
|View full text |Cite
|
Sign up to set email alerts
|

The Social Psychology of Biased Self-Assessment

Abstract: While the accreditation standards of most health-related disciplines emphasize the importance of selfawareness and accurate self-assessment, decades of social psychological research suggests that these standards will be difficult to attain. Indeed, a host of sub-conscious cognitive processes conspire to ensure that self-assessments are unjustifiably charitable. The review describes said cognitive processes, discusses the most common manifestations of biased self-assessment, and offers guidance on interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 117 publications
1
60
0
Order By: Relevance
“…However, studies have shown that feedback on success is more memorable than feedback on failure, and negative feedback is preferentially forgotten. 12 To explain why, in their study, learners who were the least skilled were particularly inaccurate in self-assessment, Kruger and Dunning postulated that metacognitive skills essential to learning and performing well are also indispensable for accurate self-assessment, and poorly performing learners cannot accurately self-assess until they are taught these metacognitive skills and their performance improves. 10 In light of these engrained deficiencies in self-assessment, Eva and Regehr argued that perhaps it is simply not possible to accurately assess one's performance without systematically and intentionally eliciting external assessment.…”
Section: Is Self-assessment By Adult Learners Accurate?mentioning
confidence: 99%
“…However, studies have shown that feedback on success is more memorable than feedback on failure, and negative feedback is preferentially forgotten. 12 To explain why, in their study, learners who were the least skilled were particularly inaccurate in self-assessment, Kruger and Dunning postulated that metacognitive skills essential to learning and performing well are also indispensable for accurate self-assessment, and poorly performing learners cannot accurately self-assess until they are taught these metacognitive skills and their performance improves. 10 In light of these engrained deficiencies in self-assessment, Eva and Regehr argued that perhaps it is simply not possible to accurately assess one's performance without systematically and intentionally eliciting external assessment.…”
Section: Is Self-assessment By Adult Learners Accurate?mentioning
confidence: 99%
“…The perfunctory use of the term “self‐assessment” to couch these various concepts has led to confusion and dismissiveness toward valid approaches to self‐inquiry/self‐analysis within the professional realm. Self‐assessment is conceptualized as, “personal, unguided reflection on performance to generate an individually derived summary of one's level of knowledge, skill, and understanding in a particular area.” 14,16 Furthermore, there are clear findings that self‐assessment, regardless of training or professional status, is inaccurate and tends toward over‐inflation 17‐20 . Conversely, SDAS is a pedagogical strategy involving self‐administration of an externally derived instrument to judge one's current level of performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, social desirability bias, the tendency of survey respondents providing an answer that is perceived as favorable, could have influenced the self‐reported HOP‐R ratings. Research has shown that unguided self‐assessment is biased favorably toward an individual due to human nature, and these biases can never be completely removed as they occur below one's awareness 18 . To mitigate social desirability bias, the facilitators discussed in‐depth that the HOP‐R was not designed for comparison amongst preceptors, that relatively few preceptors will achieve master‐level habits, and that developing habits indicate high‐quality precepting.…”
Section: Discussionmentioning
confidence: 99%
“…These learners need encouragement to “leave the nest.” Conversely, we have all witnessed learners who are overly confident and make rogue decisions that potentially endanger patient safety. These learners feel they are ready for greater autonomy but lack sufficient insights into their level of knowledge and skills . What is needed is a set of highly reliable indicators that help us make evidence‐based entrustment decisions.…”
Section: Aacp Core Entrustable Activities For New Pharmacy Graduatesmentioning
confidence: 99%